Contralateral Approach to Unruptured Superior Hypophyseal Artery Aneurysms - Chen, Sifang; Kato, Y.; Kumar, Ashish; Sinha, Rohan; Oguri, Daikichi; Oda, Jumpei; Watabe, Takeya; Imizu, Shuei; Sano, Hirotoshi; Hirose, Yuichi (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2013)
Objective To evaluate the feasibility and limitations of the contralateral approach to unruptured superior hypophyseal artery (SHA) aneurysms.Methods Data regarding eight cases of superior hypophyseal artery aneurysms operated on by a contralateral pterional approach at our center from January 2008 to September 2010 were collected and evaluated retrospectively. Of these eight cases, six were male and two were female. The mean age was 57.1 years (range 28 years to 77 years). All the aneurysms were unruptured; five were on right side and three were on left side. The surgical technique and outcome of patients were reviewed.Results All aneurysms were successfully clipped without complication and patency of all superior hypophyseal arteries was preserved. Postoperative three-dimensional computed tomography angiography revealed residual aneurysm in only one case. None of the patients had deterioration of visual acuity or field after surgery. The contralateral pterional approach was found to be appropriate for fully exposing the aneurysmal dome and neck without retraction of the optic nerve or the carotid artery in five cases. Slight retraction of the optic nerve was required in two cases, and significant manipulation of the optic nerve was required in one case.Conclusions The contralateral pterional approach for clipping of unruptured superior hypophyseal artery aneurysms is technically feasible and safe in a select group of patients where optimal results can be achieved without significant retraction of near by neurovascular structures.
Keywords: contralateral approach; superior hypophyseal artery; aneurysms